The mammalian DM domain transcription factor Dmrta2 is required for early embryonic development of the cerebral cortex. - Daijiro Konno; Misato Iwashita; Yoshiaki Satoh; Asuka Momiyama; Takaya Abe; Hiroshi Kiyonari; Fumio Matsuzaki (PLoS ONE, 2012)
Development of the mammalian telencephalon is precisely organized by a combination of extracellular signaling events derived from signaling centers and transcription factor networks. Using gene expression profiling of the developing mouse dorsal telencephalon, we found that the DM domain transcription factor Dmrta2 (doublesex and mab-3-related transcription factor a2) is involved in the development of the dorsal telencephalon. Consistent with its medial-high/lateral-low expression pattern in the dorsal telencephalon, Dmrta2 null mutants demonstrated a dramatic reduction in medial cortical structures such as the cortical hem and the choroid plexus, and a complete loss of the hippocampus. In this mutant, the dorsal telencephalon also showed a remarkable size reduction, in addition to abnormal cell cycle kinetics and defective patterning. In contrast, a conditional Dmrta2 deletion in the telencephalon, which was accomplished after entry into the neurogenic phase, resulted in only a slight reduction in telencephalon size and normal patterning. We also found that Dmrta2 expression was decreased by a dominant-negative Tcf and was increased by a stabilized β-catenin form. These data suggest that Dmrta2 plays pivotal roles in the early development of the telencephalon via the formation of the cortical hem, a source of Wnts, and also in the maintenance of neural progenitors as a downstream of the Wnt pathway.